The role of BI rate in moderating the effect of NPL, NIM, ROA, on bank credit distribution: Study on banking companies listed on the LQ45 index from 2020 to 2024 - Nia Nuzul Safitri; Muhammad Auly Hikmawan (Privietlab, 2026)
The purpose of this study to analyze the effect of Non Performing Loans (NPL), Net Interest Margin (NIM) and Return on Asset (ROA) on credit distribution, with the BI Rate serving as a moderating variabel. The population in this study includes all banking companies listed in the LQ45 index for the 2020-2024 period. This research was conducted by taking secondary data including financial reports, annual reports, and banking statistical data. The data analysis method used is panel data regression with a random effect model, processed with Eviews 13 software. The results of this study showed that simultaneously, NPL, NIM and ROA significantly influenced credit distribution. However, partially, the NPL and NIM had insignificant effect on credit distribution, while ROA had a significant positive effect on credit distribution. Futhermore, the BI Rates able to moderate the effect of NPL on credit distribution, but unable to moderate the effect of NIM and ROA on credit distribution in LQ45 index banking companies for the 2020 – 2024 period.